An Overview on the Healing Potentials of Musa sapientm (Banana) in the Treatment of Peptic Ulcer Disease - Isah U; Abdulkadir B; Raubilu I. A.; Ahmad M.A; Kabir K (UMYU Journal of Microbiology Research)
Gastric ulcer is a localized area of erosion in the stomach lining, resulting in abdominal pain, possible bleeding, and other gastrointestinal symptoms. The most common cause of gastric ulcer is Non-steroidal anti-inflammatory drugs (NSAIDs) and a stomach infection associated with the Helicobacter pylori (H. pylori) bacteria. The management of peptic ulcer disease and its complications remain a surgical challenge. Therefore, the evolution of newly discovered antiulcer drugs from medicinal plant is an attractive area, because several chemicals with anti-ulcer effect have been found in these plants, and they have shown a promising potential in the treatment of disease. Musa sapientum (Family: Musaceae), known as banana, is a familiar tropical fruit, is a treelike perennial herb that grows 5-9 m in height, with tuberous rhizome, hard, long pseudo-stem. The inflorescence is big with a reddish-brown bract, and it is eaten as vegetables, and the ripe fruits are sweet. Some studies reported that pectin and phosphatidylcholine in green banana strengthens the mucous-phospholipid layer that protects the gastric mucosa. Other studies highlight reported that leucocyanidin, a natural flavonoid from the unripe banana (Musa sapientum) pulp, protects the gastric mucosa from erosions.The present study is aim at reviewing the relevant studies on bioactive compounds in Musa sapientmwith their healing potentials in gastric ulcer diseases.